Dementia, Frailty and Aging - Marco Canevelli (Frontiers Research Topics, 2018)
The number of older subjects is rapidly increasingly worldwide. As a consequence, the nature of clinical conditions is also changing. Traditional medicine and models of care have been based on the evaluation and treatment of single and usually acute conditions occurring in relatively young individuals. Today, the usual clinical manifestation of diseases is characterized by multiple and often chronic conditions affecting older people. In this scenario, frailty and dementia have been triggering special interest both in research and clinical settings due to their high prevalence, impact on the individual's quality of life, and consequences for public health worldwide. These conditions aptly reflect the complexity of age-related pathological conditions, finding as causal factor a myriad of heterogeneous, interacting, and often still unclear pathophysiological processes. Indeed, their study is strongly affected by the difficulty to differentiate the effects of a normal aging process from eventual pathological deviations of the underlying systems. Their occurrence and trajectories over time are strongly affected by a wide array of factors and determinants that can be hardly attributed to the deficit/involvement of single biological systems and/or health domains. Moreover, environment and social factors also play a key role in the determination of phenotypes. The present Research Topic is aimed at widening our understanding of the frailty and dementia phenomena occurring with aging, in order to improve the clinical and public health approaches to these burdening conditions.